2017
DOI: 10.1016/j.nmni.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin resistance and macrolide–lincosamide–streptogramin B resistance in Staphylococcus haemolyticus among clinical strains at a tertiary-care hospital in Thailand

Abstract: Staphylococcus spp. is a major cause of nosocomial infection and sepsis. However, increasing drug resistance is becoming a challenge to microbiologists. The purpose of this study was to identify and determine antimicrobial resistance phenotypes and drug resistance genes of clinical coagulase-negative staphylococci (CoNS) isolates at Mae Sot Hospital in Tak province, Thailand. A total of 229 CoNS isolates were collected from clinical specimens during two periods in 2014 and in 2015. Staphylococcus haemolyticus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
6
18
1
Order By: Relevance
“…This finding is aligned with previous investigation demonstrating that there were increasing occurrences of coagulase negative-Staphylococcus in blood samples of patients from the hospital in US (Monsen et al 2005) and Thailand (Teeraputon et al 2017). Furthermore, coagulasenegative Staphylococcus isolates were also frequently found in samples detected in the blood samples of patients suffering from bacteremia in East Java, Indonesia (Dzen et al 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is aligned with previous investigation demonstrating that there were increasing occurrences of coagulase negative-Staphylococcus in blood samples of patients from the hospital in US (Monsen et al 2005) and Thailand (Teeraputon et al 2017). Furthermore, coagulasenegative Staphylococcus isolates were also frequently found in samples detected in the blood samples of patients suffering from bacteremia in East Java, Indonesia (Dzen et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The high frequency of these MRSH isolates is aligned with previous research suggesting the high prevalence (77.5%) of oxacillin-resistant S. haemolyticus among coagulasenegative Staphylococcus-related infections (Pereira et al 2014). Moreover, other studies also reported the high prevalence of MRSH, not only in humans (Teeraputon et al 2017), but also in animals (Lloyd 2007;Ruzauskas et al 2014;Sidhu et al 2007). Additionally, due to their acquired multi-resistance, the MRSH isolates have a crucial role in the transmission of the corresponding resistance genes leading to the widespread of more virulent pathogens, including S. aureus, in the clinical settings (Cavanagh et al 2014).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In DDST, the test inoculum with 0.5 McFarland turbidity was streaked into MHA; HiMedia, India and disks of CTX, CAZ, ATZ, cefepime, and cefpodoxime (30 µg each) were manually placed at 20 mm distance center to center surrounding a disk of amoxicillin-clavulanate (AMC; 20/10 µg). Following overnight incubation at 37°C, the test isolate was considered positive, if its zone of inhibition against any of the peripheral disk was enhanced toward AMC [ 10 ]. In case of CDM, an increase of 5 mm or more in zone diameter for CAZ/CTX in combination with clavulanic acid (CA) than that of the corresponding cephalosporin disk was interpreted as ESBL positive.…”
Section: Methodsmentioning
confidence: 99%
“…Clindamycin is the most preferred agent because of exceptional pharmacokinetic characteristics [6] and is regularly used in the management of severe infections, caused by macrolide resistant S. aureus infections including MRSA [7]. However, increasing resistance to clindamycin among MRSA strains and other Staphylococcus is a serious challenge [8]. The expression of clindamycin resistance in Staphylococcus species can be constitutive or inducible [9] [10] through erm genes which codes for ribosomal methylases [11].…”
Section: Introductionmentioning
confidence: 99%